قانون دولة إندونيسيا لحرية الأديان في ضوء إشكالية أحاديث قتل المرتد - جنة، صفية (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
The subject of the punishment of apostasy is one of the topics that has stirred controversy between classical and modern scholars. Some of them see that the hadith of the prophet which says; "Those who change their religion kill them" contradicts the teaching of the Qur'an, the Indonesian law and the Prophet's massage of mercy and comprastion. This study aims to identify the statement of the Law on Freedom of Religion in Indonesia, to examine the differences on te definition of apostasy in Islamic law and state as well as international rulings of modernity of this study used the inductive and analitical approaches. The most important findings of the research are that the Indonesian Constitution of 1945, constitutes the basic law of Indonesia, guarantees the freedom of religion. The findings indicated that, the Hadith of the apostate is true and it is not contrary to the Qoran and Indonesian law as well the Prophet's teaching. The position of the Indonesian scholars was that there is no worldly punishment for the apostate, and some of them say that repentance is obligatory, and severe punishment is only in the Hereafter.